In the previous section, we saw addition of matrices. In this section, we will see multiplication of matrix by a scalar.
This can be written in 3 steps:
1. In the previous section, we saw the industrialist and his two factories . Suppose that, the industrialist wants to triple the production in factory B.
2. The new quantities in factory B can be obtained simply by multiplying each element of matrix B by 3.
• We get:
3B = $3 \times\left[\begin{array}{r}
15 &{25} \\
30 &{37} \\
60 &{42} \\
\end{array}\right] =
\left[\begin{array}{r}
3 × 15 &{3 × 25} \\
3 × 30 &{3 × 37} \\
3 × 60 &{3 × 42} \\
\end{array}\right] =
\left[\begin{array}{r}
45 &{75} \\
90 &{111} \\
180 &{126} \\
\end{array}\right]
$
3. Using symbols, we can write:
kA = k[aij]m×n = [kaij]m×n
Negative of a matrix
This can be written in 3 steps:
1. We have seen the technique used for multiplication by a scalar. If the scalar is −1, we will get the negative of the matrix.
2. Let us see an example:
If A = $\left[\begin{array}{r}
5 &{2} \\
−3 &{7} \\
x &{4} \\
\end{array}\right]$, then:
−A = $−1 \times\left[\begin{array}{r}
5 &{2} \\
−3 &{7} \\
x &{4} \\
\end{array}\right] =
\left[\begin{array}{c}
−1 × 5 &{−1 × 2} \\
−1 × −3 &{−1 × 7} \\
−1 × x &{−1 × 4} \\
\end{array}\right] =
\left[\begin{array}{r}
−5 &{−2} \\
3 &{−7} \\
−x &{−4} \\
\end{array}\right]
$
3. We can write:
If A is a given matrix, then negative of A = −A = (−1)A
Difference of matrices
This can be written in 3 steps:
1. If A and B are two matrices, then the difference A−B is defined as:
A−B = A + (−B)
2. That means, to find the difference, we take the negative of B and then add it to A.
3. Let us see an example:
If A = $\left[\begin{array}{r}
2 &{5} &{−1} \\
6 &{3} &{9} \\
\end{array}\right]
$ and B = $\left[\begin{array}{r}
11 &{6} &{4} \\
−3 &{12} &{7} \\
\end{array}\right]
$, then find 2A−B
Solution:
$\begin{array}{ll} {~\color{magenta} 1 } &{{}} &{2A−B} & {~=~} &{2\left[\begin{array}{r} 2 &{5} &{−1} \\ 6 &{3} &{9} \\ \end{array}\right] − \left[\begin{array}{r} 11 &{6} &{4} \\ −3 &{12} &{7} \\ \end{array}\right] } \\
{~\color{magenta} 2 } &{{}} &{{}} & {~=~} &{\left[\begin{array}{r} 4&{10}&{−2}\\ 12&{6}&{18}\\ \end{array}\right] +\left[\begin{array}{r} −11&{−6}&{−4}\\ 3&{−12}&{−7}\\ \end{array}\right] } \\
{~\color{magenta} 3 } &{{}} &{{}} & {~=~} &{\left[\begin{array}{r} 4 – 11&{10−6}&{−2−4}\\ 12+3&{6−12}&{18−7}\\ \end{array}\right] } \\
{~\color{magenta} 4 } &{{}} &{{}} & {~=~} &{\left[\begin{array}{r} −7&{4}&{−6}\\ 15&{−6}&{11}\\ \end{array}\right] } \\
\end{array}
$
Properties of scalar multiplication of a matrix
If A = [aij]m×n and B = [bij]m×n are two matrices of the same order m×n, then scalar multiplication will satisfy the following two properties:
(i) k(A+B) = kA + kB
(ii) (k+l)A = kA + lA
Part (i)
•
Proof can be written in 10 steps:
1. A + B = [aij] + [bij] = [aij + bij]
We already saw this when we discussed matrix addition.
2. So k(A+B) = k[aij + bij]
• (aij + bij) is a number, written as the sum of two numbers.
• (aij + bij) represents each element in the sum matrix (A+B)
• We know that, for scalar multiplication, each element is to be multiplied by the scalar.
• So we get:
k[aij + bij] = [k(aij + bij)]
3. So the expression in (2) can be modified as:
k(A+B) = [k(aij + bij)]
4. aij and bij are numbers. So the expression in (3) can be modified as:
k(A+B) = [k aij + k bij]
5. Consider the R.H.S of the expression in (4).
It is the sum of two matrices: [k aij] and [k bij]
6. So the expression in (4) can be modified as:
k(A+B) = [k aij] + [k bij]
7. [k aij] is a matrix, which is obtained by multiplying the matrix [aij] by the scalar k. That is: [k aij] = k[aij]
• Similarly, [k bij] is a matrix, which is obtained by multiplying the matrix [bij] by the scalar k. That is: [k bij] = k[bij]
8. So the expression in (6) can be modified as:
k(A+B) = k [aij] + k [bij]
9. But k [aij] is kA. Similarly, k [bij] is kB.
10. So the expression in (8) can be modified as:
k(A+B) = kA + kB
Part (ii)
•
Proof can be written in 6 steps:
1. (k+l)A = (k+l)[aij]
This is because, we are multiplying each element of A by the scalar (k+l).
2. When we do the multiplication, we get the new matrix: [(k+l)aij].
• So the expression in (1) can be modified as:
(k+l)A = [(k+l)aij]
3. Consider the R.H.S of the expression in (2).
k and l are scalars. aij is a number.
• So the expression in (2) can be modified as:
(k+l)A = [(k aij) + (l aij)]
4. Consider the R.H.S of the expression in (3). It is the sum of two matrices.
• So the expression in (3) can be modified as:
(k+l)A = [k aij] + [l aij]
5. Consider the R.H.S of the expression in (4).
♦ The matrix [aij] is being multiplied by the scalar k.
♦ The matrix [aij] is being multiplied by the scalar l.
• So the expression in (4) can be modified as:
(k+l)A = k[aij] + l[aij]
6. The expression in (5) is same as:
(k+l)A = kA + lA
Now we will see a solved example:
Solved example 19.9
If A = $\left[\begin{array}{r}
8 &{0} \\
4 &{-2} \\
3 &{6} \\
\end{array}\right]
$ and B = $\left[\begin{array}{r}
2 &{-2} \\
4 &{2} \\
-5 &{1} \\
\end{array}\right]
$, then find the matrix X, such that 2A + 3X = 5B
Solution:
• The given expression is: 2A + 3X = 5B
• This expression can be modified as shown below:
$\begin{array}{ll} {~\color{magenta} 1 } &{{}} &{2A + 3X} & {~=~} &{5B} \\
{~\color{magenta} 2 } &{\implies} &{2A + 3X – 2A} & {~=~} &{5B – 2A} \\
{~\color{magenta} 3 } &{\implies} &{2A – 2A + 3X} & {~=~} &{5B – 2A} \\
{~\color{magenta} 4 } &{\implies} &{O + 3X} & {~=~} &{5B – 2A} \\
{~\color{magenta} 5 } &{\implies} &{3X} & {~=~} &{5B – 2A} \\
{~\color{magenta} 6 } &{\implies} &{X} & {~=~} &{\frac{1}{3}(5B – 2A)} \\
\end{array}
$
◼ Remarks:
2. The matrix -2A is added on both sides.
3. Matrix addition is commutative. So the position of -2A in the L.H.S can be changed.
4. -2A is the additive inverse of 2A. Their sum will be O.
• Now we can input the values of A and B to find X. This is shown below:
$\begin{array}{ll} {~\color{magenta} 1 } &{{}} &{X} & {~=~} &{\frac{1}{3} \left(5 \left[\begin{array}{r} 2&{-2}\\ 4&{2}\\ -5&{1}\\ \end{array}\right] - 2\left[\begin{array}{r} 8&{0}\\ 4&{-2}\\ 3&{6}\\ \end{array}\right] \right)} \\
{~\color{magenta} 2 } &{{}} &{{}} & {~=~} &{\frac{1}{3} \left(\left[\begin{array}{r} 10&{-10}\\ 20&{10}\\ -25&{5}\\ \end{array}\right] + \left[\begin{array}{r} -16&{0}\\ -8&{4}\\ -6&{-12}\\ \end{array}\right] \right)} \\
{~\color{magenta} 3 } &{{}} &{{}} & {~=~} &{\frac{1}{3} \left[\begin{array}{r} 10-16&{-10+0}\\ 20 – 8&{10+4}\\ -31&{5-12}\\ \end{array}\right]} \\
{~\color{magenta} 4 } &{{}} &{{}} & {~=~} &{\frac{1}{3} \left[\begin{array}{r} -6&{-10}\\ 12&{14}\\ -31&{-7}\\ \end{array}\right]} \\
{~\color{magenta} 5 } &{{}} &{{}} & {~=~} &{\left[\begin{array}{c} -2&{\frac{-10}{3}}\\ 4&{\frac{14}{3}}\\ \frac{-31}{3}&{\frac{-7}{3}}\\ \end{array}\right]} \\
\end{array}$
In the next section, we will see a few more solved examples.
Copyright©2024 Higher secondary mathematics.blogspot.com
No comments:
Post a Comment